Effectiveness of programs of auxiliary reproductive technologies in patients of late reproductive age - E P Beik; A G Syrkasheva; N V Dolgushina (Гинекология, 2018)
The aim of the study was to study the effectiveness of assisted reproductive technologies (ART) programs in patients of different age groups, taking into account clinical and laboratory data. Materials and methods. A prospective cohort study included 188 patients with infertility of various genesis who were stratified according to age: group 1 (n=87) - patients of late reproductive age - LRA (>35 years), group 2 (n=101) - patients of early reproductive age (≤35 years). Results. In patients with ART compared with patients with LRA, the chances of pregnancy were reduced by 2.2 times (odds ratio - OR 2.2, 95% confidence interval - CI 1.1-4.3), the chances of live birth were 2 times (OR 2.0; 95% CI 1.0-3.9). The only factor affecting the onset of pregnancy in addition to age was the number of embryos received. The threshold age at which and above which the chances of pregnancy and live birth decreased as much as possible were the age of 37 years: the OR of pregnancy 2.6 (95% CI 1.4-5.1, AUC 61.3%), OR live birth 2.6 (95% CI 1.3-5.1, AUC 60.8%). Conclusions. In patients of LRA there is a twofold decrease in the effectiveness of ART programs due to a significant decrease in the number of oocytes obtained, mature oocytes, and, accordingly, embryos.